Storage Limitation Statements: Temperature–Herbicides: PI-123/PI160, rev. 10/2009 - Fishel, Frederick M. (EDIS, 2009)
Revised! PI-123, a 10-page illustrated guide by Frederick M. Fishel, provides general temperature effects on storage properties of agricultural herbicides. A table is included that lists many of the common agricultural herbicides registered for use in Florida, with storage limitations statements. Includes additional sources of information. Published by the UF Department of Agronomy, October 2009. PI-123/PI160: Storage Limitation Statements: Temperature—Herbicides (ufl.edu)